Detection of the mcr‐1 gene in colistin‐resistant Escherichia coli from retail meat in Japan. (20th December 2017) - Nishino, Yukari; Shimojima, Yukako; Suzuki, Yasunori; Ida, Miki; Fukui, Rie; Kuroda, Sumiyo; Hirai, Akihiko; Sadamasu, Kenji
ABSTRACT: In this study, the presence of the mcr‐1 gene in Escherichia coli from retail meat in Japan was investigated. Nine E. coli isolates (eight from chickens and one from pork) carried the mcr‐1 gene on the plasmid. In six isolates from domestic chickens, mcr‐1 was located on the IncI2 plasmid, which is approximately 60 kb in size. In the remaining three isolates from imported chicken and pork, mcr‐1 was located on the IncX4 plasmid (30 kb).